Utility of diffusion weighted imaging in diagnosing subdiaphragmatic endometriosis presenting as shoulder pain - Singh, Anuradha; Das, Chandan J; Das, Bimal K; Gupta, A K (Indian Journal of Radiology and Imaging, 2017)
Extrapelvic endometriosis (EPE) is a rare entity which may potentially occur at any site. Symptomatic EPE is now increasingly being managed laparoscopically. Imaging is imperative in diagnosis as well as extent delineation prior to surgery. In addition to increasing the success rate of diagnostic laparoscopy, prior knowledge of EPE at certain sites may modify the standard surgical technique. We present here an unusual case of chronic pain in the right shoulder in a 26-year-old female caused by subdiaphragmatic endometriosis (SDE). It was noticed on conventional magnetic resonance imaging (MRI) sequences; however, due to the lack of the characteristic signal intensity, imaging findings were noncontributory. Diffusion-weighted imaging (DWI) facilitated its characterization and precisely mapped the extent of involvement. SDE should be suspected in young females presenting with cyclical shoulder pain. Due to nonspecific clinical features, it may remain undiagnosed. MRI is the imaging modality of choice in evaluation of EPE. Including DWI sequence in the MR protocol increases the diagnostic precision besides delineating the extent of involvement noninvasively.
Keywords: Extrapelvic; laparoscopy; magnetic resonance imaging